Secure Fuzzy keyword Search using an Advanced Technique over Encrypted Cloud Data (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a technology that uses the internet and central remote servers to maintain data and applications. As the data produced by individuals and enterprises that need to be stored and utilized are increasing rapidly, data owners are motivated to outsource their local complex data management systems into the cloud for its great flexibility and economic savings. To ensure that the data can be stored in the cloud securely, data owners encrypt their data before outsourcing to the cloud, which makes searching scheme  on a large amount of encrypted data a demanding task. The traditional searchable encryption schemes provide a number of approaches to search on encrypted data, but they all support only exact keyword search. Exact keyword search is unsuitable for cloud storage systems, because it doesn't allow users to make any spelling errors or format inconsistencies, and thereby reduces the system usability. The proposed system uses a wild-card based technique with edit distance as the similarity metric to obtain a fuzzy keyword sets.This solves the problems of the cloud user who search the encrypted cloud data with the help of fuzzy keyword, thereby maintaining keyword privacy.